Seepage and stability analyses of slopes within landfill area - Ho, Kai Ling (2014)
Rainfall is identified as the factor for triggering slope failure and inducing leachate from a landfill, especially in countries that experience hot and humid climatic conditions like Singapore. Many soil slopes have a characteristic of a deep groundwater table with an unsaturated zone above the groundwater table. Infiltration of rainfall causes a decrease in matric suction and shear strength of the soil, resulting in slope failure.